Impacts of Massive Earthquake 2015 AD on Coffee Production and Marketing in Western Hills of Nepal - Khanal, Arjun Prasad (International Journal of Applied Sciences and Biotechnology, 2019)
This study was conducted in Gulmi and Palpa districts in western hills of Nepal in 2017 AD with the main objective to assess the impacts of earthquake in coffee production and marketing. One hundred and sixty coffee producers were selected by a three- stage sampling procedure. In this study only 6.9 % of coffee producers had said that they had experienced impacts of massive earthquake 2015 AD on coffee production and marketing. Among the coffee producers(6.9%) who said that they had experienced the impact of earthquake 2015 AD, majority (37%) of them said that they had suffered some minor (repairable) cracks in their houses and sheds while 27% of them had said that rate of drying of water sources is accelerated after earthquake leading to shortage water for drinking and irrrigating coffee fields. Since eathquake 2015AD had minor impacts on coffee production and marketing, pre earthquake preparedness like public awareness programs, quality construction practices, preparation of new codes and standards for infrastructure design and training coffee producers, entrepreneurs and other stakeholders should be done in the study area to cope with the unforeseen consequences of earthquake in future. Int. J. Appl. Sci. Biotechnol. Vol 7(1): 114-119